The Role of Islamic Religious Education Teachers in Shaping the Character of Students at SDN Kalisari II Telagasari Karawang - Lindawati, Eneng; Rukajat, Ajat; Mansyur, Masykur H; Kejora, Muhamad Taufik Bintang (Papanda Publisher, 2025)
This study aims to explore the role of Islamic Religious Education (PAI) teachers in shaping the character of students at SDN Kalisari II Telagasari Karawang. The background of this research is the challenge in character formation of the younger generation, especially elementary school students, which is increasingly complex in the midst of rampant juvenile delinquency and moral degradation. The urgency of this research lies in the importance of character education in elementary schools as a foundation to form the personality of students with noble character and integrity. The purpose of the research is to describe how PAI teachers carry out their role in instilling Islamic character values which include honesty, responsibility, and respect through a humanist and innovative approach. This study uses a qualitative approach with an exploratory case study method. Data were obtained from interviews with PAI teachers, principals, and students in grades V and VI, in addition to direct observation and documentation of learning activities. Data analysis was carried out using constructivism approaches from Piaget and Vygotsky, with Miles and Huberman's interactive analysis models to manage the data. The validity of the data is maintained through triangulation of data from various sources. The results of the study show that PAI teachers at SDN Kalisari II Telagasari Karawang have succeeded in shaping the character of students through their various roles as educators, influencers, inspirers, innovators, and motivators. However, challenges such as limited facilities and lack of support from the home environment remain obstacles. The implications of this study show the importance of the active role of all parties, including parents and the community, in supporting character education in schools. The suggestion from this study is the need to improve supporting facilities and strengthen cooperation between schools, parents, and the community to achieve sustainable character formation.